Note on the oscillation of second-order quasilinear neutral dynamic equations on time scales - Chenghui Zhang; Tongxing Li (Нелінійні коливання, 2018)
By using a new method, we improve some results from [Saker S. H. Oscillation criteria for a second-order quasilinear neutral functional dynamic equation on time scales // Nonlin. Oscillations. – 2011. – 13, № 3. – P. 407 – 428]. З використанням нового методу покращено деякi результати, одержанi в роботi [Saker S. H. Oscillation criteria for a second-order quasilinear neutral functional dynamic equation on time scales // Нелiн. коливання. – 2010. – 13, № 3. – С. 379–399].